Improvement of Water Flow Visualization on Minihydro Power Plant Kambangan 5 MW - Thoriq Al Hafiz, A
The energy needs can’t be separated from many aspects of human activity where nowadays we need a big amount of energy especially in regions that already can access electrical energy to support their activities. Energy needs must be complemented by the the energy capacity that Indonesia government provides so that the country electricity production can satisfy the country electricity consumption. One of the effort that the Indonesia government has been doing is building a Mini-Hydro Power Plant (MHP). Kambangan MHP is one of MHP that is being under development and potentially can produce 5 MW of electricity. This final project is aiming to make an improvement on the water flow visualization of Kambangan MHP. in addition of improving the visualization, the author also design a sandtrap and forebay tank using Autodesk Inventor that is more economical in terms dimensioning. To achieve that, the aim of the design is to make the building as short as possible. On improving the water flow visualization, the author uses graphic design software Goggle sketchup and Lumion 8 to aquire a better result. After calculation process, obtained the best design of sandtrap with length, width and height such as 50 m, 6m and 2,9 m. At the same time, for forebay tank it is obtained a design that satisfy the must criteria with length, width, and height that is 69 m, 9 m, and 2,5 m. The result of static loading simulation on the water bridge yields maximum 1st principal stress, maximum deflection and smallest safety factor location with values in range of recommended values from used references and material strength.